CCC : Critical Communication Capability framework - Desler, Jim; Pultorak, David (TSO, a Williams Lea company, 2022)
"In our digital enterprise age, where technology and commerce have merged, the modern organization has transformed, so that the business is IT (information technology), and IT is the business. In this context, it is counterproductive to continue to try to handle IT major incidents, such as cyberattacks, and business-side PR nightmares, such as leaked company-sensitive information, in isolated business and IT silos. An approach that relies on separate and siloed teams, each following different playbooks without a shared visualization of the situation, is a recipe for confusion and disaster. Today's organizations need something different. They need business and IT professionals and teams to work from the same frame of reference, with a shared objective, shared information, a common visualization of the situation, a shared toolchain and one shared set of processes. Frustratingly (until now), there was no unified body of knowledge that provided a common framework for organizations to understand and handle critical situations. Acceleres created the Critical Communication Capability® (CCC) Framework to fill that gap. The CCC Framework is an extensive body of knowledge designed to provide individuals, teams and organizations with a shared frame of reference for handling crises more efficiently and effectively. Acceleres designed the CCC Framework to make critical situation handling tractable for organizations of all sizes, and to provide a shared frame of reference for assessing and establishing actual readiness and capability. It works as a unifying approach that can incorporate existing incident response processes and practices. There is no other framework like it. This publication outlines the shared approach of the CCC Framework, and includes the CCC Model, a capability assessment, an organized process for management and improvement, and extensive resource indicators and best practices"--